Physical training attenuates cardiac remodeling in rats with supra-aortic stenosis - Pacagnelli, Francis Lopes [UNESP]; Okoshi, Katashi [UNESP]; Campos, Dijon Henrique Salomé [UNESP]; Alves De Souza, Rodrigo Wagner [UNESP]; Padovani, Carlos Roberto [UNESP]; Carvalho, Robson Francisco [UNESP]; Aguiar, Andreo Fernando; Dal Pai, Maeli [UNESP]; Cicogna, Anton̂io Carlos [UNESP] (My University, 2014)
The aim of this study was to test the hypothesis that physical training (PT) attenuates cardiac remodeling and the severity of heart failure in rats with aortic stenosis. Wistar male rats were divided in sham (S, n=10), sham training (TR, n=4), aortic stenosis (AS, n=5) and aortic stenosis training (ASTR, n=5). Aortic constriction was created by placing a 0.6 mm i.d. stainless-steel clip on the ascending aorta. Eighteen weeks after surgery, when compared to the S group, AS animals presented higher left ventricle/final body weight and ventricular dysfunction, as shown by posterior wall shortening velocity. The TR and ASTR groups were then submitted to PT for 10 weeks, with the running speed and duration time gradually increasing. At the end of the experiment, HF was evaluated by clinical data, and cardiac remodeling by anatomical and functional data using echocardiography. The ASTR group showed decreased signs of HF. The ASTR in comparison to AS group showed decreased Right Ventricle/Final Body Weight, Atrium/FBW, E/A waves and increased posterior wall shortening velocity. In conclusion, our results showed that PT attenuates cardiac remodeling and the severity of HF in rats with supra-aortic stenosis. © 2013 et al.; licensee Cardiology Academic Press.
Keywords: Cardiac remodeling; Echocardiography; Physical training; Rats; Supra-aortic stenosis